More than just footnotes: Field assistants in wildlife research and conservation some stories from Arunachal Pradesh - Aiyadurai, Ambika; Pandya, Mamata (New Delhi Bookwell publications, 2023)
In Northeast India, especially Arunachal Pradesh, a large part remains unexplored due to its remoteness, difficult terrain and the necessity of multiple permissions from various authorities being a state located on the international border. The cultural diversity and the multiplicity of dialects make communication difficult in remote regions.